2015
DOI: 10.1111/cas.12619
|View full text |Cite
|
Sign up to set email alerts
|

Husband's smoking status and breast cancer risk in Japan: From the Takayama study

Abstract: The effects of smoking on breast cancer remain unclear. We assessed the associations of subjects' or husbands' smoking status with breast cancer incidence in a population-based prospective study in Japan. The subjects were 15 719 women aged 35 years or older. The follow up was conducted from September 1992 to March 2008. Cancer incidence was mainly confirmed through regional population-based cancer registries. Breast cancer was defined as code C50 according to the International Classification of Diseases and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…There is increasing evidence which supports the link between BC risk and heavy smoking over a long period of time (American Cancer Society, 2016). This was confirmed in several articles demonstrating a clear association between BC risk and exposure, either active or passive, to tobacco smoke (Mizoo et al, 2013;Pimhanam et al, 2014;Tong et al, 2014;Wada et al, 2015).…”
Section: Modifiable Risk Factorsmentioning
confidence: 57%
See 1 more Smart Citation
“…There is increasing evidence which supports the link between BC risk and heavy smoking over a long period of time (American Cancer Society, 2016). This was confirmed in several articles demonstrating a clear association between BC risk and exposure, either active or passive, to tobacco smoke (Mizoo et al, 2013;Pimhanam et al, 2014;Tong et al, 2014;Wada et al, 2015).…”
Section: Modifiable Risk Factorsmentioning
confidence: 57%
“…Huang et al, (2014) reported that among participants from China, of non-agricultural population, and second industry output; in contrast, incidence was negatively correlated with the percentage of population employed in primary industry (Fei et al, 2015). Other modifiable risk factors including active or passive smoking (Mizoo et al, 2013;Pimhanam et al, 2014;Tong et al, 2014;Wada et al, 2015), high body mass index (BMI) (Mizoo et al, 2013;Sangrajrang et al, 2013;Suzuki et al, 2013;Wang et al, 2013b;Anothaisintawee et al, 2014;Wada et al, 2014;Fu et al, 2015), use of oral contraceptives (Bhadoria et al, 2013;Anothaisintawee et al, 2014;Poosari et al, 2014), high perceived level of stress, and low level of physical later age at either first live birth, or at first pregnancy and last pregnancy were associated with increased BC risk (p-trend=0.002, 0.015, 0.008, respectively). Among participants from Japan, BC was increased in women who performed mixed feeding (HR 1.12, 95% CI, 0.92-1.37, p-trend=0.014) or feeding only with formula (HR 1.80, 95% CI, 1.14-2.86, p-trend=0.014) compared with women who only breastfed (Sugawara et al, 2013).…”
Section: Reproductive History and Breastfeedingmentioning
confidence: 99%
“…Results for various ETS exposure indices were reported. Seven studies (Alberg et al, 2004 ; Hirayama, 1987 ; Jee et al, 1999 ; Nishino et al, 2014 ; Roddam et al, 2007 ; Tong et al, 2014 ; Wada et al, 2015 ) only recorded exposure from the spouse or partner, while 10 further studies (Delfino et al, 2000 ; Gammon et al, 2004 ; Gram et al, 2005 ; Lash & Aschengrau, 1999 , 2002 ; Lin et al, 2008 ; Mechanic et al, 2006 ; Pirie et al, 2008 ; Sandler et al, 1985 ; Woo et al, 2000 ) only considered at-home exposure. The other studies collected more extensive information.…”
Section: Resultsmentioning
confidence: 99%
“…The abstract by Woo et al ( 2000 ) does not make the position clear for the other nested study. Given the length of follow-up was 10 years or more in three prospective studies (Hanaoka et al, 2005 ; Rosenberg et al, 2013 ; Wada et al, 2015 ), some of the women would have reached the menopause between interview and breast cancer diagnosis, so the results from the two types of study are not completely comparable. This problem is less so for Pirie et al ( 2008 ), where follow-up was only for 3.5 years.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 11 In addition, husband’s smoking is a significant risk factor for non-respiratory ETS-related diseases for the nonsmoking wife, such as coronary artery disease (CAD), 12 stroke 13 and breast cancer. 14 …”
Section: Introductionmentioning
confidence: 99%